SISTEM INFORMASI GEOGRAFIS SARANA PADA KABUPATEN PASAMAN BARAT - Harison; Ahmad Syarif (ITP Press, 2016)
West Pasaman has a wide area of ± 3864.02 km2 and a population of about ± 365 129 inhabitants, the government has established a means for people in West Pasaman, including education facilities, health facilities and police facilities. As for the number of facilities that have been established in the field of as many as 355 educational facilities, health care facilities and fields as many as 21 police were 7 facilities. The number of facilities built to make building sites scattered across the West Pasaman, with but there are still many people who do not know the location of the facilities built. To that end, the technology is used Geographic Information System (GIS) to map the location, and displays the information infrastructure constructed by the government of West Pasaman. With the GIS, the location and the facilities built can be summarized in a web page attractive and dynamic, within the website, both the government and the community will get location information, distance to the location, as well as the means of what is built in the form of images, as well as getting The latest news about west Pasaman. GIS technology utilizes Google Maps as a place to display the specified location through the point coordinates of the location means it is built, then the coordinates are stored in a database by using MySQLi as Database, after the data is stored, then the website is displayed using the programming language PHP and HTML.